Ortotanásia no direito penal brasileiro - Massola, Luis Felipe Grandi (2012)
The right to life is a fundamental right guaranteed by constitution, but, exceptionally, can be relativized. That can be seen from the analysis of some devices that permeate the legal parental rights, both constitutional and infra. In this sense, this paper seeks to demonstrate the urgent need for orthothanasia to be approved explicitly in the Penal Code as a new cause of unlawful exclusionary and thus treated as a new kind of relative right to life. The right to have a dignified death represents the real and effective application of the principle of human dignity to those who are severely ill with signs of imminent death, avoiding unnecessary suffering cruelty of therapy. From this perspective devices are analyzed in the New Code of Medical Ethics that legitimize the adoption of orthothanasia from the standpoint of medical ethics and its relations with the Draft of the Special Part of the Penal Code which gives the orthothanasia legal cause of unlawful exclusionary . Finally, considerations are made about the need to adopt the so-called palliative care also under criminal perspective, harmonizing the principles highlighted with the notion of humanizing the death process